Understanding Brand Activism as A Marketing Strategy: A Literature Review - Iriani, Nadya; Nasution, Reza Ashari (Journal of Business Management Education (JBME), 2023)
In response to the digital technology-driven shift in younger generations and the evolving values of citizen-consumers, brands are now expected to align with individual identities, fostering deeper connections with customers. This has given rise to brand activism as a pivotal marketing trend for differentiation in a competitive landscape. This article investigates the state of brand activism in marketing strategy literature while identifying research gaps. Conducting a systematic review of 1010 articles following PRISMA guidelines, this research explores the effects of brand activism on consumer behavior and attitudes, consumer-brand relationships, and financial performance. Additionally, this research examines the benefits and risks of employing brand activism as a marketing strategy.